Race, gender and empire in American detective fiction - Gruesser, John Cullen, 1959- (McFarland & Co., Inc., Publishers, 2013)
"This book highlights detection's malleability by analyzing the works of particular groups of authors from specific time periods written in response to other texts. Specifically, it traces the roles that gender, race and empire have played in American detective fiction from Edgar Allan Poe's works through the myriad variations upon them published before 1920 to hard-boiled fiction"--